Leadership through effective communication - LIM, Han Boon Kevin (Institutional Knowledge at Singapore Management University, 2023)
Charismatic leadership oratory is critical in aligning the organisational vision and goals for business sustainability. This research focuses on charismatic leadership, particularly on oratory leading to charismatic perception by the audience. This research seeks to provide future leaders with a better perspective of the multigenerational workforce in an effort to customise the rhetorical process for this diverse workforce to enhance charismatic perception, thereby promoting organisational communication. The audience in prior studies has been treated as a homogeneous unit (Clark & Greatbatch, 2011; Groß et al., 2015), without distinguishing between different generational groups and their respective receptiveness to a leadership oratory. There has been little focus on audience preferences and especially on the diverse multigenerational audience with differing cultures, social backgrounds and technological preferences. Understandably, different communication styles relate differently to the way an individual thinks, processes and interacts in the iterative process of information exchange. This may mislead a leader to assume they have reached concerted alignment with the audience in the messaging. Further, although prior leadership oratory researchers have demonstrated the effectiveness and operationalisation of rhetoric devices, the studies were speaker focused, focusing more on the follower effects. Conversely, the present research examines the rhetorical preferences of the audience, especially those from younger generations, to provide leaders with a better perspective of audiences’ preferences and enable to enhance their oratory effectiveness. ASEAN is the world’s fastest-growing economy, with an estimated GDP of US$2.4 trillion in 2013, an estimated population of over 600 million people, and the third-largest workforce in the world, behind China and India, with a large percentage of its population belonging to young generations. With Southeast Asia accounting for approximately 9% of the world’s population with a median age of 30 years old, a large part of the region’s workforce is in the Generations Y (Naim & Lenka, 2018) and Z age groups. With Singapore being a key member state of ASEAN, we can expect a steady stream of younger foreign workers into Singapore seeking employment. Therefore, it is important for future leaders to appreciate the oratorical process, especially with younger generations. This research comprises of two surveys and a series of interviews to determine whether diversity in the multigenerational audience translates to diversity in charismatic perception. The studies sought to identify the preferences and perspectives of the diverse audience, especially Generations Y and Z, who form the next workforce waves after Generation X, to help future leaders craft their oratory to enhance its charismatic perception and improve organisational communication. The results showed that multigenerational diversity does result in different charismatic perception, but the difference was mild. The research demonstrated that the younger generations have higher preference towards verbal and non-verbal rhetorical delivery techniques over content. Finally, this research recommends a list of rhetorical techniques for the virtual communication setting—the new normal.